If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11t + 5)(6t + -18) = 0 Reorder the terms: (5 + 11t)(6t + -18) = 0 Reorder the terms: (5 + 11t)(-18 + 6t) = 0 Multiply (5 + 11t) * (-18 + 6t) (5(-18 + 6t) + 11t * (-18 + 6t)) = 0 ((-18 * 5 + 6t * 5) + 11t * (-18 + 6t)) = 0 ((-90 + 30t) + 11t * (-18 + 6t)) = 0 (-90 + 30t + (-18 * 11t + 6t * 11t)) = 0 (-90 + 30t + (-198t + 66t2)) = 0 Combine like terms: 30t + -198t = -168t (-90 + -168t + 66t2) = 0 Solving -90 + -168t + 66t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), '6'. 6(-15 + -28t + 11t2) = 0 Factor a trinomial. 6((-5 + -11t)(3 + -1t)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-5 + -11t)' equal to zero and attempt to solve: Simplifying -5 + -11t = 0 Solving -5 + -11t = 0 Move all terms containing t to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -11t = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -11t = 0 + 5 -11t = 0 + 5 Combine like terms: 0 + 5 = 5 -11t = 5 Divide each side by '-11'. t = -0.4545454545 Simplifying t = -0.4545454545Subproblem 2
Set the factor '(3 + -1t)' equal to zero and attempt to solve: Simplifying 3 + -1t = 0 Solving 3 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1t = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1t = 0 + -3 -1t = 0 + -3 Combine like terms: 0 + -3 = -3 -1t = -3 Divide each side by '-1'. t = 3 Simplifying t = 3Solution
t = {-0.4545454545, 3}
| x^2+7x=3 | | 2x^4+5x^2-3=0 | | 90t=50(t+2) | | -3x-5=-14 | | 280=2(x+40)+(2x) | | (y-11)-(y+8)=10y | | -2(2p-4)=3(p+12) | | 0.05x-0.01y=0.6 | | 8x^2-34x+35=0 | | 3x+x+(6x-13)=180 | | 3x^3+24=0 | | -2=-4+t | | x^4+7x^2+1=0 | | (x+4)+6=22 | | 200=5r | | 200r=5 | | 200=5+r | | 8(9m+4)=-4(3m+8) | | .2x+2y=2.8 | | 200=5tr | | 6-2(3x-4)=-16 | | .2x+.5y=-.2 | | -2-8+14(-2)= | | -15x^3+7x^2+12=0 | | m^4-81=0 | | 12+7x^2+-15x^3=0 | | 2x^2+x+20=0 | | (8x-5)(64x^2-80x+25)=0 | | x^2+12x+52=0 | | 4xy^2-25x=0 | | x^2+4-12-36=0 | | (x-3)(x-3)-1=0 |